Exploring example models of cross-sector, sessional employment of pharmacists to improve medication management and pharmacy support in rural hospitals - Tan, A.; Emmerton, Lynne; Hattingh, L.; La Caze, A. (2015)
INTRODUCTION: Many rural hospitals in Australia are not large enough to sustain employment of a full-time pharmacist, or are unable to recruit or retain a full-time pharmacist. The absence of a pharmacist may result in hospital nurses undertaking medication-related roles outside their scope of practice. A potential solution to address rural hospitals' medication management needs is contracted part-time ('sessional') employment of a local pharmacist external to the hospital ('cross-sector'). The aim of this study was to explore the roles and experiences of pharmacists in their provision of sessional services to rural hospitals with no on-site pharmacist and explore how these roles could potentially address shortfalls in medication management in rural hospitals. METHODS: A qualitative study was conducted to explore models with pharmacists who had provided sessional services to a rural hospital. A semi-structured interview guide was informed by a literature review, preliminary research and stakeholder consultation. Participants were recruited via advertisement and personal contacts. Consenting pharmacists were interviewed between August 2012 and January 2013 via telephone or Skype for 40-55 minutes.RESULTS: Thirteen pharmacists with previous or ongoing hospital sessional contracts in rural communities across Australia and New Zealand participated. Most commonly, the pharmacists provided weekly services to rural hospitals. All believed the sessional model was a practical solution to increase hospital access to pharmacist-mediated support and to address medication management gaps. Roles perceived to promote quality use of medicines were inpatient consultation services, medicines information/education to hospital staff, assistance with accreditation matters and system reviews, and input into pharmaceutical distribution activities. CONCLUSIONS: This study is the first to explore the concept of sessional rural hospital employment undertaken by pharmacists in Australia and New Zealand. Insights from participants revealed that their sessional employment model increased access to pharmacist-mediated medication management support in rural hospitals. The contracting arrangements and scope of services may be evaluated and adapted in other rural hospitals.